Kritik Sosial dalam Kumpulan Puisi Malu Aku Jadi Orang Indonesia Karya Taufiq Ismail - Idal, Idal; Asri, Yasnur; Zulfadhli, Zulfadhli (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purposes of this research are (1) to describe social critique forms in the collection of poetries â€œMalu (Aku) Jadi Orang Indonesiaâ€ (MAJOI) by Taufiq Ismail, (2) to explain the causing factors of social critique happened in the collection of poetries â€œMalu (Aku) Jadi Orang Indonesiaâ€ (MAJOI) by Taufiq Ismail. The research data are poetry lines in the collection of poetries â€œMalu (Aku) Jadi Orang Indonesiaâ€ (MAJOI) by Taufiq Ismail. The cources of data are twenty of one hundred poetries in the collection of poetries MAJOI that are taken from the book of the collection of poetries â€œMalu (Aku) Jadi Orang Indonesiaâ€ (MAJOI) by Taufiq Ismail published by Yayasan Indonesia the second publishing in year 2000. The research data are collected by using descriptive method. The finding of the research shows that the forms of social critique are (1) poverty and job vacancy problems, (2) crime and its solution, and (3) bureaucracy, politic, and security problem. Whereas, causing factors of social critique happened are (1) economic gap in society, (2) the tendency of government policy in overcoming the crisis of economy, (3) the militaristic that is dominat in government.